Adolescents who engage exclusively in healthy weight control behaviors: Who are they?. Issue 1 (December 2016) - Lampard, Amy; Maclehose, Richard; Eisenberg, Marla; Larson, Nicole; Davison, Kirsten; Neumark-Sztainer, Dianne
Abstract Background Little is known about the exclusive adoption of healthy weight control behaviors in the absence of unhealthy weight control behaviors among adolescents. The current study aimed to determine (i) the prevalence of the exclusive adoption of healthy weight control behaviors, (ii) the pattern of eating behaviors and physical activity reported by those engaging exclusively in healthy weight control behaviors, and (iii) the socio-demographic and psychosocial factors associated with the exclusive use of healthy weight control behaviors among adolescents. Methods In a large and diverse population-based sample of US adolescents (N = 2793) who participated in EAT 2010 (Eating and Activity in Teens) the current study examined the exclusive use of healthy weight control behaviors, which included healthy eating behaviors (eating more fruits and vegetables, eating less high-fat foods, eating less sweets, drinking less soda, and being aware of portion sizes) and engaging in physical activity for the purpose of weight management. Data were analyzed using multinomial logistic regression in STATA. Results Overall, 24.0 % of girls and 29.2 % of boys exclusively used healthy weight control behaviors in the absence of unhealthy weight control behaviors. The exclusive use of healthy weight control behaviors was more prevalent among girls who were not overweight (27.5 %) as compared to girls who were overweight (21.0 %) or obese (17.5 %), controlling for age, socio-economic status, and ethnicity/race. In addition, the exclusive use of healthy weight control behaviors was more prevalent among girls and boys who had lower body dissatisfaction, higher self-esteem and lower depressive symptoms. Conclusion Findings indicate that psychosocial health and body satisfaction may be important targets for promoting the exclusive use of healthy weight control behaviors among adolescents.